Factors of Sleep Quality of University Students: A Comparison Between Malaysia and India - Kee, Daisy Mui Hung; Martin, Garry; Ting, Felicia; Tiong, Hannah; Hah, Shi En; Bokil, Saloni; Nair, Rajesh Kumar (AIBPM Publisher, 2021)
Good sleep quality has a vital role in enhancing cognitive skills. Poor nighttime sleep quality affects the physical and cognitive health of students. This research examined the factors affecting university students' sleep quality between Malaysia and India. This research is quantitative in nature. A total of 81 University students from Malaysia and 74 University students from India responded. The findings revealed that the sleep quality among students was above average. The findings also showed that lifestyle behavior and environment were the important factors affecting the sleep quality of university students. The conclusion was drawn of the factors affecting the sleep quality of university students.